Effects of Modified Melatonin Release on Human Colostrum Neutrophils to Induce Death in the MCF-7 Cell Line - Waynner O. Sousa; Mahmi Fujimori; Tassiane C. Morais; Milena B. Santos; Gabriel F. S. Rodrigues; Katleyn P. G. Silva; André H. F. Torres; Adenilda C. Honorio-França; Eduardo L. França (International Journal of Cell Biology)
Cancer is one of the diseases with the highest mortality rate today, with breast cancer being the second most common type among the Brazilian population. Due to its etiological complexity and inefficiency of treatments, studies have focused on new forms of treatment. Among these forms of treatment, hormonal therapy seems to be an excellent auxiliary mechanism in tumoricidal activity, and melatonin has great potential as a modulator of the immune system. Thus, the present study is aimed at evaluating the effect of the hormone melatonin on the coculture of colostrum polymorphonuclear cells and MCF-7 cancer cells and evaluates the effect of this hormone using a modified transport system. A feasibility analysis was performed by fluorescence microscopy at three cell incubation times, 2 hours, 24 hours, and 72 hours. The measurement of cytokines in the cell supernatant occurred in 24 hours, and the apoptosis assay was performed in 72 hours using flow cytometry. The results showed higher levels of cell viability in groups treated with melatonin and less viability in groups containing a coculture of polymorphonuclear cells and MCF-7 after 72 hours of incubation. Furthermore, the apoptosis and necrosis rates were higher in coculture polymorphonuclear and MCF-7 cells, especially in groups containing microemulsion as a modified release agent. These data suggest that melatonin, especially if associated with a modified release system, has immunomodulatory effects on human colostrum polymorphonuclear cells. These cells can play a crucial role in the resolution of the tumor through their mediation and inflammatory action.